Evaluating the training courses of the use of educational techniques from the perspective of trainees - Alabdullah, Fawaz; fawwaz Aat, Maya (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aimed to evaluate the training courses of the use of educational technology from the perspective of the trainees, and to find out the effect of some variables on it .In order to a chieve the objectives of this research, the descriptive analytical method was used by designing a questionnaire consisting of 50 statements distributed on six axes. The study sample was consisted of 171 administrators and teachers at the schools of the Governorate of Lattakia who followed one or more courses of the use of educational techniques. The most important research results were: The order of the axes of the questionnaire came as the following: The extent of the advantage of the course, The content of the course programme, The general level of the performance of the lectures, The course place The course objectives, The course time. The evaluation of the training courses of the use of educational techniques from the perspective of the trainees came generally at an acceptable degree. There were no differences which are statistically significant between the average responses of the sample of the questionnaire of evaluating the training courses of the use of educational techniques according to the variables of the job and the number of years of experience. There were no differences which are statistically significant between the average responses of the sample of the questionnaire of evaluating the training courses of the use of educational techniques according to the variables of the number of courses adopted and the scientific and educational qualification except for the axis of (The extent of the advantage of the course) as some differences in favor of those who followed one or more courses and for those who have the diploma of educational qualification were found out.